Give blood today or save lives tomorrow: Matching decision and message construal level to maximize blood donation intentions. Issue 3 (3rd July 2017) - Czeizler, Amalia; Garbarino, Ellen
ABSTRACT: The research extends construal theory by testing if a match between the temporal construal framing of a blood donation decision and a blood donation request leads to higher donation intentions than a mismatch. Results show participants considering future donation who read an abstract donation request have significantly higher donation intentions than those who read a concrete request. Conversely, participants considering donating today who read a concrete donation request have significantly higher donation intentions than those who read an abstract request. This study confirms the importance of matching the construal framing of the communication to the temporal framing of the decision.